Direct measurement of Stokes–Einstein diffusion of Cowpea mosaic virus with 19 µs‐resolved XPCS. (10th October 2022) - Switalski, Kacper; Fan, Jingyu; Li, Luxi; Chu, Miaoqi; Sarnello, Erik; Jemian, Pete; Li, Tao; Wang, Qian; Zhang, Qingteng
Abstract : Stokes–Einstein diffusion of active Cowpea mosaic virus was measured up to a 69 nm length‐scale with 19 µs‐resolved X‐ray photon correlation spectroscopy. Abstract : Brownian motion of Cowpea mosaic virus (CPMV) in water was measured using small‐angle X‐ray photon correlation spectroscopy (SA‐XPCS) at 19.2 µs time resolution. It was found that the decorrelation time τ( Q ) = 1/ DQ 2 up to Q = 0.091 nm −1 . The hydrodynamic radius R H determined from XPCS using Stokes–Einstein diffusion D = kT /(6πη R H ) is 43% larger than the geometric radius R 0 determined from SAXS in the 0.007  M K3 PO4 buffer solution, whereas it is 80% larger for CPMV in 0.5  M NaCl and 104% larger in 0.5  M (NH4 )2 SO4, a possible effect of aggregation as well as slight variation of the structures of the capsid resulting from the salt–protein interactions.